The "complex-in-a-complex" cations [(acac)2M?Ru6-(p-iPrC6H4Me)6(tpt)2(dhbq)3]6+: a trojan horse for cancer cells - Therrien, Bruno; Süss-Fink, Georg; Govindaswamy, Padavattan; Renfrew, Anna K.; Dyson, Paul J. (My University, 2008)
The cytotoxicities of the large cationic arene-ruthenium prismatic cage [Ru6(p-iPrC6H4Me)6(tpt)2(dhbq)3]6+ (tpt = 2,4,6-tris(pyridin-4-yl)-1,3,5-triazine, dhbq = 2,5-dihydroxy-1,4-benzoquinolato; 16+), and its "complex-in-a-complex" derivs. [(acac)2M-1]6+ (M = Pd, Pt; acac = acetylacetonate), are evaluated in comparison with free [M(acac)2]. The differences in cytotoxicity suggest that, like a "Trojan Horse", leaching of the guest from the cage once inside a cell accelerates and increases the cytotoxic effect. [on SciFinder(R)]
Keywords: hydroxyquinolato bridged cymene ruthenium pyridinyltriazine complex prepn reaction; palladium platinum acetylacetonate hydroxyquinolato bridged cymene ruthenium binuclear prepn; antitumor activity palladium platinum acetylacetonate hydroxyquinolato bridged cymene ruthenium; crystal mol structure platinum acetylacetonate hydroxyquinolato bridged cymene ruthenium